Genotypic variability for cassava tuberous root development in two lowaltitude and midaltitude savanna sites of Nigeria - Akparobi, S.O.; Ekanayake, I.J.; Togun, A. (2002)
Cultivated cassava (Manihot esculenta Crantz) genotypes are relatively sensitive to low temperature stress injury. The objective of this field study was to elucidate tuberous root development and growth differences among improved and local genotypes under lowland (higher seasonal temperature) and mid-altitude (lower seasonal temperature) savanna growing conditions. Therefore genotypic differences of the onset of tuberization, tuberous root number and dry tuberous root weight changes of 12 cassava genotypes were examined at 2 field sites (Jos: 18°C ±5°C, Ibadan: 270C ± 6"C) and 2 seasons (1994/95 and 1995/96). Genotypic differences were significant (P<0.05) among the genotypes both across locations and within locations for all traits. Significant differences (P<0.05) in root number and weight were observed between the 2 locations irrespective of sampling period (3, 6, 9, and 12 months after planbng). Early initiation of tuberous roots was observed in TMS 4(2) 1425, TMEI and TMS 30572 at both locations. The improved clones TMS 30572, TMS 4(2) 1425, TMS 91934 and landraces TMEI and Oko-lyawo had higher root numbers than the others. At Ibadan, TMS 30572, TMS 4(2) 1425 and TMEI completed tuberization earlier while at Jos, TMS 30572 and TMEI were the earliest to tubenze. TMS 30572, TMS 4(2) 1425, TMS 91934 and TME 1 had higher root number and weight than other genotypes at Ibadan. In mid-altitude sites, Danwaru, TMEI and TMS 30572 performed better. Our results confilTl1ed that low temperatures affected both developmental event associated with tuberization and growth such as root number and size. Mid-altitude conditions induced a delay in the onset of completion of tuberization. The desirable traits associated with mid-altitude adaptation were early initiation of tuberous roots, larger number of tuberous roots, and high dry root yield. Some of the genotypes identified as adapted to mid-altitudes with seasonally low temperatures may be useful as parental sources in breeding programs targeted for mid or high altitudes.